Invasive Streptococcus agalactiae ST283 infection after fish consumption in two sisters, Lao PDR [version 1; peer review: 2 approved] - Viengmon Davong; Jasmin Hiestand; Manophab Luangraj; Swaine L. Chen; Othila Rasphone; Andrew J.H. Simpson; Timothy Barkham; Valy Keoluangkhot; David A.B. Dance (Wellcome Open Research, 2022)
Background: Streptococcus agalactiae is a normal commensal of the human gastro-intestinal and female genital tracts. It causes serious disease in neonates and pregnant women, as well as non-pregnant adults. Food-borne outbreaks have also been described. A link between invasive Group B streptococcus (GBS) infection in humans caused by S. agalactiae serotype III-4, sequence type 283 (ST283) and the consumption of raw fresh-water fish was first described in Singapore in 2015. Case presentation: We report the simultaneous occurrence of acute fever and myalgia in two sisters who were visiting Laos. Both were found to have invasive GBS ST283 infection, confirmed by blood culture. Infection was temporally linked to fish consumption. They responded well to intravenous antibiotics within 48 hours. Conclusions: Food-borne transmission of Streptococcus agalactiae is an important and under-recognised source of serious human disease throughout Southeast Asia and possibly beyond.